Developing strategies for construction waste management in sustainable projects / Muhammad Hakimi Rosdi - Rosdi, Muhammad Hakimi (2021)
The increasing amount of construction waste management has created a major environmental concern that necessitates a better method for dealing with the wastes that are generated. Construction trash, which is generated throughout the construction process, adds significantly to municipal solid waste. Many past research has proved that only a few contractors use contemporary waste management methods in sustainable projects. The aim of the research is an attempt to highlight the appropriate strategies of construction waste management in sustainable projects. Objectives of the research are to investigate the current practices of waste management implementation in the sustainable project to determine challenges during the implementation of waste management in the sustainable project and to recommend the appropriate strategies for implementing waste management in a sustainable project. The research was carried out around Federal of Kuala Lumpur where quantitative analysis was used to obtain data for this study findings. A sum of 80 questionnaires were handed out and 54 of them returned back the survey where the percentage of response are at 74%. Data are analysed by using SPSS software where descriptive analysis are used. From the findings, the researcher finds that respondents who are adopting a waste management technology is the highest in current practices of waste management implementation in the sustainable project.